2015
DOI: 10.1155/2015/412595
|View full text |Cite
|
Sign up to set email alerts
|

Right Hepatic Artery: A Cadaver Investigation and Its Clinical Significance

Abstract: The right hepatic artery is an end artery and contributes sole arterial supply to right lobe of the liver. Misinterpretation of normal anatomy and anatomical variations of the right hepatic artery contribute to the major intraoperative mishaps and complications in hepatobiliary surgery. The frequency of inadvertent or iatrogenic hepatobiliary vascular injury rises with the event of an aberrant anatomy. This descriptive study was carried out to document the normal anatomy and different variations of right hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 16 publications
1
46
1
Order By: Relevance
“…[ 2 ] The normal RHA arises from the PHA, whereas an RRHA arises from other sources. [ 11 ] ARHA and RRHA are well described in the literature by Michels, [ 16 ] Suzuki et al, [ 18 ] Mäkisalo et al, [ 19 ] Hiatt et al, [ 17 ] Gruttadauria et al, [ 9 ] Covey et al, [ 8 ] Varotti et al, [ 20 ] Kishi et al, [ 21 ] Koops et al, [ 22 ] Ahn et al, [ 6 ] Abdullah et al, [ 23 ] López-Andújar et al, [ 24 ] Winston et al, [ 25 ] De Cecco et al, [ 26 ] Egorov et al, [ 27 ] Saba and Mallarini, [ 28 ] Gümüs et al, [ 29 ] Loschner et al, [ 10 ] Dandekar et al, [ 15 ] Mugunthan et al, [ 11 ] Thangarajah and Parthasarathy, [ 30 ] as well as some case reports (Tables 1 and 2 ). [ 3 – 39 ] By systematic review of these articles and case reports, we identified the various origins of ARHA and RRHA, as well as their incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] The normal RHA arises from the PHA, whereas an RRHA arises from other sources. [ 11 ] ARHA and RRHA are well described in the literature by Michels, [ 16 ] Suzuki et al, [ 18 ] Mäkisalo et al, [ 19 ] Hiatt et al, [ 17 ] Gruttadauria et al, [ 9 ] Covey et al, [ 8 ] Varotti et al, [ 20 ] Kishi et al, [ 21 ] Koops et al, [ 22 ] Ahn et al, [ 6 ] Abdullah et al, [ 23 ] López-Andújar et al, [ 24 ] Winston et al, [ 25 ] De Cecco et al, [ 26 ] Egorov et al, [ 27 ] Saba and Mallarini, [ 28 ] Gümüs et al, [ 29 ] Loschner et al, [ 10 ] Dandekar et al, [ 15 ] Mugunthan et al, [ 11 ] Thangarajah and Parthasarathy, [ 30 ] as well as some case reports (Tables 1 and 2 ). [ 3 – 39 ] By systematic review of these articles and case reports, we identified the various origins of ARHA and RRHA, as well as their incidence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] The RRHA can arise from LGA, GDA, CHA, [ 9 ] SA, [ 12 ] RA, inferior mesenteric artery (IMA), [ 11 ] SMA, [ 13 ] CT, [ 14 ] right phrenic artery (RPA), [ 8 ] or directly from the AA. [ 15 ] However, these 2 variant arteries always occur independently in humans. Variant anatomy in patients involving both the ARHA and RRHA has never been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…An accessory right hepatic artery (aRHA) refers to an additional artery of the right liver, while a normal branch derives from a proper hepatic artery (PHA) [ 3 ]. In general, aRHA arises mainly from the superior mesenteric artery (SMA), but may also branch off from the celiac trunk (CT), common hepatic artery (CHA), renal artery (RA), gastroduodenal artery (GDA), abdominal aorta (AA), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial irrigation of the liver. Bianchi et al (2014), Rachanee Chanasong (2014), Dandekar et al (2015), Yan et al (2015), Durand-López (2016) and Alghamdi et al (2017) found: Arterial irrigation comes from the hepatic artery proper in 70 % of cases; from the hepatic artery proper and a branch of left gastric artery (A12.2.12.013) in 25 %, from the hepatic artery proper plus a branch from left gastric artery plus a branch from superior mesenteric artery (A12.2.12.053) in 3 %, and from the hepatic artery proper and a branch from superior mesenteric artery in 2 %. The hepatic artery proper is divided into left and right branches; the left branch is short and less voluminous than the right branch.…”
Section: Resultsmentioning
confidence: 99%